Metaphorical Figure of Speech Learning through a Collection of Poems Setitis Air Mata, Seulas Senyum by Kahlil Gibran - Nurulanningsih, Nurulanningsih; Salsabila, Putri (Asian Journal of Applied Education (AJAE), 2025)
This research discusses the metaphors used in poems Setitis Air Mata, Seulas Senyum by Kahlil Gibran. The type of research used in this study is qualitative descriptive research. The results show the use of metaphors in the collection of poems Setitis Air Mata, Seulas Senyum by Kahlil Gibran there are 12 findings. Anthropomorphic metaphors were found as many as 3 findings, animal metaphors were found as many as 3 findings, metaphors from concrete to abstract were found 3 findings, and anesthesia metaphors were found as many as 3 findings. Through this poem students can use this novel as a learning medium and this research can be used as additional material for teachers to provide learning understanding, especially in metaphorical materials.